Tectono-Sedimentary Evolution of the Cenozoic Basins in the Eastern External Betic Zone (SE Spain) - Manuel Martín-Martín; Francesco Guerrera; Mario Tramontana (Geosciences, 2020)
Four main unconformities (1–4) were recognized in the sedimentary record of the Cenozoic basins of the eastern External Betic Zone (SE, Spain). They are located at different stratigraphic levels, as follows: (1) Cretaceous-Paleogene boundary, even if this unconformity was also recorded at the early Paleocene (Murcia sector) and early Eocene (Alicante sector), (2) Eocene-Oligocene boundary, quite synchronous, in the whole considered area, (3) early Burdigalian, quite synchronous (recognized in the Murcia sector) and (4) Middle Tortonian (recognized in Murcia and Alicante sectors). These unconformities correspond to stratigraphic gaps of different temporal extensions and with different controls (tectonic or eustatic), which allowed recognizing minor sedimentary cycles in the Paleocene–Miocene time span. The Cenozoic marine sedimentation started over the oldest unconformity (i.e., the principal one), above the Mesozoic marine deposits. Paleocene-Eocene sedimentation shows numerous tectofacies (such as: turbidites, slumps, olistostromes, mega-olistostromes and pillow-beds) interpreted as related to an early, blind and deep-seated tectonic activity, acting in the more internal subdomains of the External Betic Zone as a result of the geodynamic processes related to the evolution of the westernmost branch of the Tethys. The second unconformity resulted from an Oligocene to Aquitanian sedimentary evolution in the Murcia Sector from marine realms to continental environments. This last time interval is characterized as the previous one by a gentle tectonic activity. On the other hand, the Miocene sedimentation was totally controlled by the development of superficial thrusts and/or strike-slip faults zones, both related to the regional geodynamic evolutionary framework linked to the Mediterranean opening. These strike-slip faults zones created subsidence areas (pull-apart basin-type) and affected the sedimentation lying above the third unconformity. By contrast, the subsidence areas were bounded by structural highs affected by thrusts and folds. After the third unconformity, the Burdigalian-Serravallian sedimentation occurred mainly in shallow- to deep-water marine environments (Tap Fm). During the Late Miocene, after the fourth unconformity, the activation of the strike-slip faults zones caused a shallow marine environment sedimentation in the Murcia sector and a continental (lacustrine and fluvial) deposition in the Alicante sector represented the latter, resulting in alluvial fan deposits. Furthermore, the location of these fans changed over time according to the activation of faults responsible for the tectonic rising of Triassic salt deposits, which fed the fan themselves.